Psychometric properties of fertility desire scale (FDS) developed for Iranian parents - Seyed Abolhassan Naghibi; Maryam Khazaee-Pool; Mahmood Moosazadeh (BMC, 2019)
Abstract Background Fertility choice is a critical women's right. Although researchers have studied the positive effects of fertility desire, its different components have, unfortunately, been neither established nor implemented for parents. A reliable and valid scale is required to measure this vital aspiration of a couple. This study aims to develop and evaluate the psychometric properties of the Fertility Desire Scale (FDS), which is designed to assess fertility desire among Iranian parents. Methods A multi-phase instrument developmental approach was used to develop this scale in 2017. The items for the questionnaire were generated using three approaches: a qualitative study, an interview with an expert panel, and a comprehensive literature review. To provide a draft form of the questionnaire, we performed face and content validity analyses. The questionnaire validation was conducted on a sample of married women and men, recruited from public places affiliated with the Mazandaran province. Finally, measurement and analyses of exploratory and confirmatory factors, internal consistency reliability, item-scale correlation, and test-retest reliability of the questionnaire were performed to complete the validation process. Results Thirty-five items were initially developed on the basis of the interviews with the expert panel and the literature review. The questionnaire was subsequently reduced to include 27 items after performing the content and face validity testing. The exploratory factor analysis (EFA) identified four factors (positive childbearing motivations, preferences, childbearing worries, and social beliefs) comprising 19 items that jointly accounted for 55.44% of the observed variance. The confirmatory factor analysis (CFA) also revealed the suitable model fit for the data. The Cronbach's alpha coefficient for the subscales ranged from .83 to .86, and the intraclass correlation coefficient (ICC) ranged from .88 to .92; these coefficients are well above the acceptable thresholds. Conclusion Results from this validation study demonstrated that the FDS is a valid and reliable questionnaire for measuring fertility desire that can be used in clinical practice, as well as in similar future studies.